The role of gestural timing in non-coronal fricative mergers in Southwestern Mandarin: Acoustic evidence from a dialect island. (November 2021) - Rao, Dongmei; Shaw, Jason A.
Highlights: Analysis of spectral variation in fricatives showing labial-velar merger. Center of Gravity for [f] lowered by posterior rimes, especially [oŋ]. Center of Gravity for [x] raised by labialization in [x w ]. [x w ] environment leads merger of [x] with [f]. Pathway to change integrates phonetic variation with diachronic facts. Abstract: Merger between a voiceless labiodental fricative, [f], and a voiceless velar fricative, [x], is common across languages, including many varieties of Chinese, particularly those spoken in Southwestern China. The sound changes that lead to merger in Southwestern Mandarin varieties are bidirectional: in some, [f] becomes [x]; in others [x] becomes [f]. We conducted a study of phonetic variation in one such variety, Zhongjiang (中江) Chinese, which has been reported to merge labialized [x], i.e., [x w ], to [f]. Our results confirm this basic pattern while revealing additional nuances, including a new environment, [_oŋ], which conditions merger in the opposite direction, [x] becomes [f], and new phonetic details. In particular, [x] exhibits a particularly low spectral Center of Gravity (CoG) and [f] exhibits a wide range of spectral variation, including tokens with low CoG, characteristic of a velar constriction. We interpret these patterns in the context of areal variation, proposing a pathway to change that relates spectral variation attributable to gestural overlap to diachronic observations of labio-velar merger.